Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider a cousin of the Chebyshev function:

$$t(x) = \sum \alpha_i $$ such that $$ p_i^{\alpha_i }= x, \ p_i \leq x$$

I speculated that $ t(x) \sim C(x)$, the composites $\leq(x)$

If $t(x) = \sum \alpha_i = \sum \log_{p_i}x = \sum \frac{\ln x}{\ln p_i } = \ln x \sum \frac{1}{\ln p_i}\sim \ln x $ Li(x) $ \sim \ln x \frac{x}{ \ln x} \sim x \sim C(x) $.

After some thought the above seems okay, and also for

$$r(x) = \sum \beta_j $$ such that $$c_j^{\beta_j }= x, \ c_j \leq x$$ in which $c_j$ is the jth composite (excluding 1).

Because s = $\sum\frac{1}{\ln c_j} $ is nearly $\sum \frac{1}{\ln x}$ we would expect that $\ln x\sum \frac{1}{\ln c_j}\sim x$ also.

My lingering question is this: why would

$\sum \beta_j - x \sim \pi(x)$, or equivalently, $\ln x\sum \frac{1}{\ln c_j}- x \sim \pi(x)$?

A typical calculation: x= 900,000, r(x) = 971141, r(x) - x = 71141 and $$\pi(x) = 71274$$

share|cite|improve this question
The number of composites less than $x$ is asymptotic to $x$, so I don't see what isn't satisfying. I'm sure $\sum_{p\lt x}(1/\log p)$ is discussed in intro analytic number theory texts, but I'm away from my references so I can't be more specific. – Gerry Myerson Dec 30 '11 at 3:40
@GerryMyerson: I worked through most of my questions about the above but edited in one lingering question. Thanks for any thoughts. – daniel Dec 30 '11 at 21:48
It should be easy to get error terms for $\sum(1/\log m)$. Then it should be possible to find good estimates for $\sum(1/\log p)$ in the literature. Once you have both of these you'll be able to subtract and get something about the sum over the composites. – Gerry Myerson Dec 31 '11 at 4:18
up vote 2 down vote accepted

First, I wanted to point out that most of what you wrote is not correct. $t(x)\sim\frac{x}{\log x}$, not $\sim x$. This is because if $\sum_{p\leq x}\sim \text{li(x)}$, then we expect that by dividing by $\log p$, I will get $\text{li}(x)/\log(x)$, and then $t(x)\sim \text{li}(x)$. Also, the computations are way off. Checking on Matlab, I have that: $$r(900000)=9000090.94\dots$$ and hence $$r(900000)-900000=90.94\dots$$ You did not remove the primes correctly. Now lets prove all of this in full.

Some Rigorous Proofs: Lets go over everything in detail. The two series you are considering are

$$t(x)=\log x\sum_{p\leq x}\frac{1}{\log p}$$ and $$r(x)=\log x\sum_{1<c\leq x}\frac{1}{\log c},\ \text{where }c>1\text{ is composite.}$$ Notice that $r(x)+t(x)=\sum_{2\leq n\leq x}\frac{1}{\log n}$ so we need only evaluate $\sum_{2\leq n\leq x}\frac{1}{\log n}$ and $\sum_{p\leq x}\frac{1}{\log p}$. First

Lemma 1: $$\sum_{2\leq n\leq x}\frac{1}{\log n}=\text{li}(x)-C+O\left(\frac{1}{\log x}\right)$$ where the constant $C$ is given by $$C=\int_{2}^{\infty}\frac{\left\{ t\right\} }{t\left(\log t\right)^{2}}dt.$$

Proof: We may write this as a Riemann-Stieltjes integral: $$\sum_{2\leq n\leq x}\frac{1}{\log n}=\int_{2}^{x}\frac{1}{\log t}d\left[t\right]=\int_{2}^{x}\frac{1}{\log t}dt-\int_{2}^{x}\frac{1}{\log t}d\left\{ t\right\}$$ where $\left[t\right]$ and $\left\{ t\right\}$ are the floor and fractional parts of $t$, respectively. Using integration by parts and the definition of $\text{li}(x)$ this is $$\text{li}(x)-\frac{\left\{ x\right\} }{\log x}-\int_{2}^{x}\frac{\left\{ t\right\} }{\left(\log t\right)^{2}}dt.$$

Remark: Although I have not done the computation myself, I believe the constant $C$ can be cleaned up in terms of other known constants.

Lemma 2: We have that $$\sum_{p\leq x}\frac{1}{\log p}=\text{li}\left(x\right)-\frac{x}{\log x}+O\left(xe^{-c\sqrt{\log x}}\right).$$

Proof: If $\theta(x)=\sum_{p\leq x}\log p$, we may write $$\sum_{p\leq x}\frac{1}{\log p}=\int_{2}^{x}\frac{1}{\left(\log t\right)^{2}}d\theta\left(t\right)=\int_{2}^{x}\frac{1}{\left(\log t\right)^{2}}dt+\int_{2}^{x}\frac{1}{\left(\log t\right)^{2}}d\left(\theta(t)-t\right).$$ For the first term, notice that by integration by parts $$\int_{2}^{x}\frac{1}{\log t}dt=\frac{x}{\log x}+\int_{2}^{x}\frac{1}{\left(\log t\right)^{2}}dt.$$ For the second term we can use integration by parts along with the prime number theorem which states that $\theta(t)-t=O\left(xe^{-c\sqrt{\log x}}\right).$ Then $$\int_{2}^{x}\frac{1}{\left(\log t\right)^{2}}d\left(\theta(t)-t\right)=\frac{\left(\theta(x)-x\right)}{\left(\log x\right)^{2}}+2\int_{2}^{x}\frac{\theta(t)-t}{t\left(\log t\right)^{3}}dt+O(1)$$ $$=O\left(xe^{-c\sqrt{\log x}}\right),$$ and the lemma follows.

Consequences: Putting these two lemmas together, we find that: $$t(x)=\text{li}(x)\log x-x+O\left(xe^{-c\sqrt{\log x}}\right),$$ $$r(x)+t(x)=\text{li}(x)\log x -C\log x+O\left(xe^{-c\sqrt{\log x}}\right).$$ We have to put in the extra error term since we are subtracting $r(x)$, and this will consume the $C\log x$ term since it is larger. Hence $$r(x)=x+O\left(xe^{-c\sqrt{\log x}}\right)$$ and $$r(x)-x=O\left(xe^{-c\sqrt{\log x}}\right).$$

I hope that helps,

share|cite|improve this answer
The Riemann Hypothesis gives $\theta(t)-t=O(x^{(1/2)+\epsilon})$, so I'd expect the agreement between $r(x)$ and $x$ to be better in practice than what we can actually prove. – Gerry Myerson Jan 1 '12 at 16:52
@GerryMyerson: Certainly, if we assume RH then $$r(x)-x=O_\epsilon\left(x^{\frac{1}{2}+\epsilon}\right)$$ for any $\epsilon$. (Of course the other direction is true as well, and this is equivalent to RH) – Eric Naslund Jan 1 '12 at 16:58
@EricNaslund: I will be working through this for a while. Lemma 2 is especially interesting. Thanks. – daniel Jan 2 '12 at 2:14
@daniel: I just wanted to add, notice in particular that since it is $\text{li}(x)-\frac{x}{\log x}$ the sum will be asymptotic to $\frac{x}{(\log x)^2}$ – Eric Naslund Jan 2 '12 at 5:23
@EricNaslund: The last integr. by parts in Lemma 2--if v is (1/log t)^2, isn't the coefficient of the integral 2 rather than 1/2, since dv is -2(1/log t)^(-3)(1/t)? – daniel Jan 6 '12 at 12:28

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.